Research framework on KMS use: an approach anchored on the interplays between engineered and emergent organizational factors - Oyebisi, Ishaq Oyefolahan; Mahmud, Murni (2013)
The rapid changes in business operations and the frequency at which new products and services are introduced to market by competing organizations continue to emphasize the importance of effective management of knowledge that resides in every organization. Knowledge Management Systems (KMS) which are tools enabling the management of organizational knowledge is gaining importance because of the speed at which knowledge needs to be leveraged to aid organizations in sustaining competitiveness in the mist of stiff competition. Despite this importance and the acknowledgement of social processes as enablers of Knowledge Management (KM) processes, little attention has been given to how organizational factors interplay to promote the development of knowledge efficacy and effectiveness of KMS utilization in organization. This paper is an attempt to provide conceptual understanding on how motivating job design (engineered factor), as well as collaborative and innovative norms (emergent factors) interplay to promote knowledge efficacy and effectiveness in organizational use of KMS. Based on the proposed conceptualized framework, several propositions are postulated for future empirical study.